Administration’s Effects of Ethanol Extract of Cissus quadrangularis Salisb on Growth of Lumbal Bone in Ovariectomized Rats - Mustafa Sabri (Jurnal Natural, 2013)
Cissus quadrangularis Salisb is a medicinal plant which has been used traditionally to cure bone fracture by Acehnese. This study was carried out to investigate the administration effects of Cissus quadrangularis Salisb extract (CQSE) on the histology of lumbar bone in ovarectomized rats. There were 16 female rats (Rattus norvegicus) as samples and were then divided into 4 groups of treatment, with 4 replications each. K0 consisted of ovarectomized rats without CQSE supplementation, whereas K1, K2 and K3 consisted of ovarectomized rats administrated with 300, 500 and 700 mg/kg body weight CQSE for 60 days, respectively. On the day 61st, all rats were euthanized with chloroform and their fourth lumbal bones were collected for histological preparation. Parameters observed were densities of active osteoblast, passive osteoblast and osteoclast. The results of this study showed that density of active osteoblast of rats in K3 (27.25 ± 2.75) was significantly higher (P0.01) than rats in K0 (1.75 ± 1.25), K1(4.00 ± 1.41), and K2 (8.50 ± 7.40), respectively. There was no significant difference (P0,05) of passive osteoblast density among rats in K0 (16.50 ± 6.13), K1 (41.00 ± 6.48), K2 (44.50 ± 16.34), and K3 (39.00 ± 15.23). Osteoclast density of rats in K0 (85.25 ± 25.91) was significantly higher (P0,05) than that of rats in K1 (52.50 ± 16.66), K2 (51.00 ± 7.16), and K3 (50.75 ± 9.20). In conclusion, consecutive administration of 700 mg/kg body weight of CQSE extract for 60 days might increase active osteoblast density in ovarectomized rats.